Virtual reality for assessing emergency medical competencies in junior doctors – a pilot study - Franca Keicher; Joy Backhaus; Sarah König; Tobias Mühling (International Journal of Emergency Medicine)
Abstract Background The teaching and assessment of clinical-practical skills in medical education face challenges in adequately preparing students for professional practice, especially in handling emergency situations. This study aimed to evaluate the emergency medical competencies of junior doctors using Virtual Reality (VR)-based scenarios to determine their preparedness for real-world clinical situations. Methods Junior doctors with 0–6 months of professional experience participated in one of three VR-based emergency scenarios. These scenarios were designed to test competencies in emergency medical care. Performance was automatically assessed through a scenario-specific checklist, and participants also completed self-assessments and a clinical reasoning ability test using the Post-Encounter Form. Results Twenty-one junior doctors participated in the study. Results showed that while general stabilization tasks were performed well, there were notable deficiencies in disease-specific diagnostic and therapeutic actions. On average, 65.6% of the required actions were performed correctly, with no significant variance between different scenarios. Participants achieved an average score of 80.5% in the Post-Encounter-Form, indicating a robust ability to handle diagnostic decisions. Self-assessments did not correlate significantly with objective measures of competency, highlighting the subjective nature of self-evaluation. Conclusion VR-based simulations can provide a detailed picture of EMC, covering both diagnostic and therapeutic aspects. The findings of this pilot study suggest that while participants are generally well-prepared for routine tasks, more focus is needed on complex case management. VR assessments could be a promising tool for evaluating the readiness of new medical professionals for clinical practice.